2013
DOI: 10.1097/inf.0b013e318290bf63
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Bacteremia in Hospitalized Pediatric Patients With Community-acquired Pneumonia

Abstract: Background National guidelines recommend obtaining blood cultures in children hospitalized with moderate or severe community-acquired pneumonia (CAP). The objectives of this study were to determine the prevalence of bacteremia in children, identify factors associated with bacteremia and quantify the influence of positive blood cultures on clinical management in children hospitalized with CAP. Methods This multicenter retrospective study included children from 60 days to 18 years of age requiring hospitalizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
1
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(91 citation statements)
references
References 17 publications
3
80
1
7
Order By: Relevance
“…32 Two studies examined radiographic features in CAP, 33,34 1 evaluated antimicrobial use in the treatment of CAP, 35 and 1 examined infl ammatory markers in CAP. 36 Four studies evaluated bacteremia in children with CAP, [37][38][39][40] 1 study examined management of CAP, 41 and another focused on severe CAP admissions to the ICU. 42 The majority of studies used observational cohort design, except for 1 study that used a nested case-control design.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…32 Two studies examined radiographic features in CAP, 33,34 1 evaluated antimicrobial use in the treatment of CAP, 35 and 1 examined infl ammatory markers in CAP. 36 Four studies evaluated bacteremia in children with CAP, [37][38][39][40] 1 study examined management of CAP, 41 and another focused on severe CAP admissions to the ICU. 42 The majority of studies used observational cohort design, except for 1 study that used a nested case-control design.…”
Section: Resultsmentioning
confidence: 99%
“…Contaminants accounted for 14.7% of isolates, which in individual studies ranged from 5.9%-75% of positive BCs. 27,28,35,[38][39][40][41] However, reporting varied across studies, with contaminants documented in all US studies but reported in only 3 studies conducted outside of the United States.…”
Section: Positive Bcsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, less than 10 % of children hospitalized for uncomplicated CAP have documented bacteremia [33, 34••]. When a pathogen is isolated, culture results may not change antibiotic selection [35,32]. Others have suggested a strategy that limits blood cultures to children at risk for severe or complicated bacterial disease [31••, 32].…”
Section: Bacterial Testing Blood Culturesmentioning
confidence: 99%